Proceedings of the First ACM Workshop on Information Hiding and Multimedia Security 2013
DOI: 10.1145/2482513.2482538
|View full text |Cite
|
Sign up to set email alerts
|

Document authentication using graphical codes

Abstract: This paper proposes to investigate the impact of the channel model for authentication systems based on codes that are corrupted by a physically unclonable noise such as the one emitted by a printing process. The core of such a system is the comparison for the receiver between an original binary code, an original corrupted code and a copy of the original code. We analyze two strategies, depending on whether or not the receiver use a binary version of its observation to perform its authentication test. By derivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…The most used authentication test for CDP is the comparison of original CDP with binarized version of P&S CDP [12]. But thanks to research interest on this topic, several original copydetection measures were suggested [3].…”
Section: Copy Detection Measuresmentioning
confidence: 99%
“…The most used authentication test for CDP is the comparison of original CDP with binarized version of P&S CDP [12]. But thanks to research interest on this topic, several original copydetection measures were suggested [3].…”
Section: Copy Detection Measuresmentioning
confidence: 99%
“…In previous works [11,6] we modeled the mentioned authentication system as a hypothesis testing problem and we derived tight bounds on its performance. The authentication system works as follow: a binary authentication image is constructed from a randomly chosen binary sequence x N in {0, 1} N by the legitimate source.…”
Section: Studied Problemmentioning
confidence: 99%
“…2), are respectively modeled by probability distributions conditioned to the original data P Y /X,Θ and P Z/X,Θ , Θ andΘ are sets of parameters, taken in Ξ, specifying the devices in each case. As pointed in [11], the receiver observes one of the two possible images y N or z N and have to decide whether it comes from the legitimate source or not (see (5) in Fig. 2), supposed that the models P Y /X,Θ and P Z/X,Θ are known.…”
Section: Studied Problemmentioning
confidence: 99%
See 1 more Smart Citation